Apprehending the Instability and Divergence in Philippine Jurisprudence via Feminist Theories of Public Emotion and Standpoint - Galero, Fritz; Sunga, Agnes (Social Sciences and Development Review, 2023)
Instability and divergence in the decisions rendered by courts of justice are typically accepted with reservations. To better understand this episode of variance, the paper set out to explore how the exercise of judicial discretioncontributes to the unpredictability and conflict in jurisprudence or decisions rendered by the Supreme Court of the Republic of the Philippines. Using a case study approach that enabled a comparative examination of two (2) landmark cases decided by the Philippine Supreme Court, which were sourced from the Supreme Court Reports Annotated (SCRA), it was learned that judicial discretion, understood as a variety of public emotion, carries with it normative elements that are, then, grasped via the intersection of the prescriptive and descriptive components of the law. Additionally, the paper had also taken the liberty of utilizing the standpoint theory that enabled the detection of variance and its locus in the individual, at the micro level, at the level of everyday transactions. These perspectives stand to enrich when taken as an adjunct to the widely accepted view that circumstances obtained in each case or controversy determine the latter’s outcome and, thus, occasions an experience of a heightened sensibility towards the dynamism of jurisprudence or decisions rendered by the Supreme Court of the Republic of the Philippines.
Keywords: prescriptive legal positivism; public emotion; discretion; jurisprudence; standpoint theory